Youth and Parent Perceptions of Parenting in Childhood Cancer Survivors and Healthy Peers - Schepers, Sasja A. (Support Care Cancer, 2018)
PURPOSE: Having a child diagnosed with cancer may have a long-term impact on parenting practices. The aims of this study were to (a) examine possible differences in youth and parent perceptions of parenting between childhood cancer survivors and healthy comparisons, (b) determine the concordance between youth and parent perceptions of parenting, and (c) explore differences in parent-youth concordance between survivors and healthy comparisons. METHODS: Participants were youth aged 8–18 years (N=170 childhood cancer survivors, N=114 healthy comparisons), and one of their parents. All patients were ≥ 3 years from diagnosis (M=6.52, SD=3.60). Both youth (Parental Bonding Instrument (PBI)) and parents (Parenting Relationship Questionnaire (PRQ)) reported on their perceptions of parenting. Two separate MANCOVA’s (PBI and PRQ) were conducted to determine possible differences between childhood cancer survivors and healthy peers. Concordance between youth and parent perceptions of parenting was examined. RESULTS: Survivors did not differ from healthy peers in their perception of parental care and overprotection (p = .890). Likewise, parents in the survivor and healthy peer groups did not differ in their perceptions of involvement, attachment, communication, confidence, or relational frustration (p = .360). Youth’s report of a caring parent-child relationship was positively associated with parent-reported involvement, attachment, communication, and parenting confidence, and negatively associated with parent-reported relational frustration. Youth perceived overprotection was positively associated with parent-reported relational frustration. No differences were found in parent-youth concordance between survivors and healthy comparisons. CONCLUSION: A history of childhood cancer does not appear to adversely influence parenting behavior, as perceived by both youth and their parents.